Maturation Selection Bias and Injury in a Secondary School Sports Academy - Cooper, Tom; Whatman, Chris (New Zealand Federation of Sports Medicine, 2025)
The aim of this study was to examine maturation selection bias and injury in a secondary school sports academy. Male students (n=98) from a Boys High School had their anthropometric measurements taken (standing height and weight). Estimated percent of predicted adult height (%PAH) was derived using the Khamis-Roche method. Percent of PAH was used to estimate maturity status and timing. Participants also completed an injury history survey designed to record injuries experienced over the previous three months. Most participants were early maturers (65%, n=64), suggesting a bias towards the selection of more mature players. Late maturers accounted for only 1% (n=1) of players selected. Injury history identified that 60% (n=52) of participants had been injured in the three months prior to data collection but there was no association with maturity status. Increased awareness of the potential for maturity-based selection bias in secondary school team sports is needed.
Keywords: 1106 Human Movement and Sports Sciences; 3202 Clinical sciences; 4207 Sports science and exercise